Equity in REDD+: Varying logics in Tanzania - Rantala, S.; Kontinen, T.; Korhonen-Kurki, Kaisa; Mustalahti, I. (Wiley, 2015)
Equity is frequently cited as one of the key design aspects of environmental governance regimes. In the context of Reduced Emissions from Deforestation and Forest Degradation (REDD+), a forest‐based climate change mitigation instrument, the manner in which ‘equity’ is understood will be of critical importance for the impacts and acceptance of REDD + policies and initiatives. Whereas the concept has been extensively studied in the academic literature, references to equity in REDD + policy debates and documents are often vague, leaving room for various interpretations and modes of implementation. In our case study of the Tanzanian national REDD + policy domain, we provide a conceptual framework based on an institutional logics approach for analysing the various underlying rationalities in the ‘equity in REDD+’ debate. We apply it to demonstrate how the involved policy actors draw from heterogeneous equity logics in their support for and opposition to different governance models, highlighting the importance of precise contextualization and operationalization of broad international principles in national REDD + initiatives. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment.